Spatial Literacy and Error Patterns in Elementary 3D Geometry: Foundations for Local Instructional Theory - Octaria, Dina; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil (Edumatica : Jurnal Pendidikan Matematika, 2026)
Spatial literacy is a vital math skill for students to learn during their three-dimensional geometry education. The two skills remain essential, yet most fifth-grade students struggle with spatial tasks. This challenge restricts their conceptual growth. The research examines fifth-grade students’ spatial literacy abilities and their error patterns to provide evidence for developing a Local Instructional Theory (LIT) on three-dimensional geometry. The research included 118 fifth-grade students (aged 10-11 years) from two public primary schools in Palembang who participated in a descriptive quantitative study with error analysis. The research data came from student performance on the spatial literacy diagnostic test and their error analysis records. The researchers applied descriptive statistics to determine average scores and establish performance levels for visualisation, reasoning, and communication skills. The researchers categorised student mistakes into four categories: procedural errors, conceptual errors, representational errors and communicative errors. The students produced results indicating significant differences in their performances. Students failed to perform basic procedural tasks, including spatial form comparison and application of formal notation, while they struggled with complex visualisation and the development of multiple-step spatial thinking and conceptual understanding. Students’ learning difficulties manifest as systematic errors, indicating that their challenges stem from complex, interconnected issues rather than random mistakes. The research results demonstrate that students need instruction which teaches them to develop their visualisation abilities, their reasoning skills, and explanatory competencies. The designs serve as an essential tool for uniting procedural fluency with conceptual understanding, leading to better spatial literacy in early geometry education.